Project Manager Profile Characterization in Energy Sector (2016)
This article describes and analyzes the fundamental characteristics of the project-manager profile in energy sector. This article includes a literature review, qualitative analysis based on expert's interviews, quantitative analysis based on surveys of project managers and finally, analysis and benchmarking of internationally recognized modern project management standards. This exercise contributes to the culture of project development and project management, specifically the recognition of the project manager's role and contribution to the successful project delivery. The identified profile shows satisfactory levels of education, training and experience, with some weaknesses in managing project complexities (environmental, risks, methodologies, communication and social responsibility).